Action & character according to Aristotle : the logic of the moral life - Flannery, Kevin L. (Catholic University of America Press, 2013)
Aristotle, according to the author, depicts the way in which human acts of various sorts and in various combinations determine the logical structure of moral character. Some moral characters - or character types - manage to incorporate a high degree of practical consistency; others incorporate less, without forfeiting their basic orientation toward the good. Still others approach utter inconsistency or moral deprivation, although even these, insofar as they are responsible for their actions, retain a core element of rationality in their souls. According to Aristotle, moral character depends ultimately on the structure of individual acts and on how they fit together into a whole that is consistent - or not consistent - with justice and friendship. -- From publisher's description.